Provisioning healthy and diverse foods to the urban poor in Nigeria : a practice-based perspective on informal ready-to-eat food vending - Adeosun, Kehinde Paul (Wageningen University & Research, 2023)
In most developing countries’ cities, informal ready-to-eat food vending is very prominent and considered the most commonly used food supply channel, particularly among the poor (Fellows et al., 2012). Informal ready-to-eat food vending is an important system of food provision in developing countries that can play a role in access to healthy and diverse ready-to-eat foods among different socio-economic groups (Patel, 2014). It is the cheapest, most convenient, and most available food supply channel and one that fits best into the everyday life of urban dwellers. Informal ready-to-eat foods are receiving increasingly high acceptance, patronage, or engagement among the urban poor because they are affordable and convenient (Mathye and Maliwichi, 2015). Moreover, this system of food provisioning is expanding as the urban population in developing countries keeps on increasing through urbanization. Most urban populace cannot do without the presence of food vending outlets as these are the most available, affordable, and accessible ready-to-eat food supply channel for them. However, according to existing literature, this food supply channel is inadequate in terms of quantity and quality. For example, shortcomings were found in terms of poor hygiene practices and the supply of food that is of low nutritional quality (Mwangi et al., 2002; Story, 2008; Muyanja et al., 2011; Lucan et al., 2014; Kolady et al., 2020). This thesis, therefore, focuses on understanding everyday out of-home food vending and consumption practices among the urban poor and how the health and diversity of supplied food can be improved.